EDGE ENHANCEMENT TECHNIQUES BASED ON MINIMUMEIGEN VALUES OF THE IMAGE PIXELS - Hadi, Gheidaa (Iraqi Journal of Science, 2024)
In this paper, an modify minimum eigen values technique is introduced to detectedge points and outline the boundaries of objects within an image. The presentededge method is performed by utilizing 3×3 and 5×5 windows, and counting theeigenvalues within each. The minimum eigen value then adopted to replace thewindow’s center which finally produces an image. Two types of image samples wereused to test the propused method. Sobel type of edge detection then was applied andthe results were better in edge detection obviously.